セールロンダーネ サンチ チガク チョウサ ホウコク 1988 (JARE-29) - 浅見, 正雄; アサミ, マサオ; 牧本, 博; マキモト, ヒロシ; 安仁屋, 政武; アニヤ, マサム; 林, 正久; ハヤシ, マサヒサ; 飯村, 友三郎; イイムラ, ユウザブロウ; 林, 孝; ハヤシ, タカシ; et al. (1988)
P(論文) 第29次南極地域観測隊の夏季地学調査隊(10名編成)は, 1988年1月6日から2月3日までの29日間, セールロンダーネ山地の中の未調査域である東部地域(バルヒェン地域)を中心に, 地質・地形・測地・隕石の4分野にわたる調査を実施した。またこの調査に先立って, 測地部門の2名は, 1987年12月21日と22日に山地東部および中部地域においてピラタス機による航空写真撮影を行った。好天に恵まれ, 大きな事故のなかったことも幸いして, 各部門ともほぼ計画どおりの調査・作業を終えることができた。本報告では, 今回の調査における設営面を含めた行動の概要を中心に記述し, 併せて各部門の成果も簡単に紹介する。 The ten-man summer field party of the 29th Japanese Antarctic Research Expedition (JARE-29) carried out geological, geomorphological and geodetic field work and a meteorite search in the Sør Rondane Mountains, mainly east of Byrdbreen (71°40'-72°15'S, 26°30'-28°E) from January 6 to February 3,1988 (29 days). In addition, on December 21 and 22,1987,two surveyors from our party took aerophotographs in the eastern and central parts of the mountains, using a "Pilatus Porter" plane. Being favored by good weather and no serious accident, we were able to complete most of the work that we had planned. This paper is a description of the field operation including logistics and a brief report on the geological, geomorphological and geodetic field work, meteorite search and aerophotography. departmental bulletin paper